Energy Efficiency Evaluation of SISO and MIMO between LTE-Femtocells and 802.11n Networks - Siyi Wang; Weisi Guo; O'Farrell, T. (2012 IEEE 75th Vehicular Technology Conference (VTC Spring), 2012)
The objective of this paper is to provide the methodology and results that is used to evaluate a scalable energy performance comparison of LTE-femtocells and 802.11n with both SISO and MIMO antenna configurations. The performance is derived in a multi-user and multi-cell wireless communication system. A system level LTE-femtocell simulator has been developed and an analytical model to evaluate 802.11n network performances has been proposed. It is shown that 1 Femtocell Access Point consistently perform better than 1 802.11n Access Point. This may be explained by the centralised resource allocation and channel access methods used by femtocells compared to distributed methods and CSMA/CA used by 802.11 networks. Generally, SISO deployment is more energy efficient than Alamouti MIMO 2×2.